Using synthetic biology to overcome barriers to stable expression of nitrogenase in eukaryotic organelles - Xiang, Nan (Proc Natl Acad Sci U S A, 2020)
Engineering biological nitrogen fixation in eukaryotic cells by direct introduction of nif genes requires elegant synthetic biology approaches to ensure that components required for the biosynthesis of active nitrogenase are stable and expressed in the appropriate stoichiometry. Previously, the NifD subunits of nitrogenase MoFe protein from Azotobacter vinelandii and Klebsiella oxytoca were found to be unstable in yeast and plant mitochondria, respectively, presenting a bottleneck to the assembly of active MoFe protein in eukaryotic cells. In this study, we have delineated the region and subsequently a key residue, NifD-R98, from K. oxytoca that confers susceptibility to protease-mediated degradation in mitochondria. The effect observed is pervasive, as R98 is conserved among all NifD proteins analyzed. NifD proteins from four representative diazotrophs, but not their R98 variants, were observed to be unstable in yeast mitochondria. Furthermore, by reconstituting mitochondrial-processing peptidases (MPPs) from yeast, Oryza sativa, Nicotiana tabacum, and Arabidopsis thaliana in Escherichia coli, we demonstrated that MPPs are responsible for cleavage of NifD. These results indicate a pervasive effect on the stability of NifD proteins in mitochondria resulting from cleavage by MPPs. NifD-R98 variants that retained high levels of nitrogenase activity were obtained, with the potential to stably target active MoFe protein to mitochondria. This reconstitution approach could help preevaluate the stability of Nif proteins for plant expression and paves the way for engineering active nitrogenase in plant organelles.